Social environment exposure to electronic cigarettes and its association with e-cigarette use among adolescents in Shanghai, China - Dai, Luojia; Lu, Weiyi; Wang, Juanjuan; Zhang, Lulu; Zhu, Jingfen (Frontiers in Public Health, 2022)
Objective: This study investigated adolescents’ social-environmental exposure to e-cigarettes in association with e-cigarette use in Shanghai, China. We also explored these differences by gender and school type. Methods: 16,123 students were included by a stratified random cluster sampling, and the number was weighted according to selection probability. Association between social environment exposure and e-cigarette use was examined by multivariate logistic regressions. Results: There were 35.07%, 63.49%, 75.19%, 9.44% and 18.99% students exposed to secondhand e-cigarette aerosol (SHA), e-cigarette sales, e-cigarette information, parents’ and friends’ e-cigarette use. Students exposed to SHA (aOR=1.73, 95% CI 1.40-2.14), e-cigarette sales from ≥2 sources (aOR=1.55, 95% CI 1.18-2.03), e-cigarette information exposure from ≥2 sources (aOR=1.39, 95% CI 1.05-1.83), and having a social e-smoking environment (friends’ e-cigarette use: aOR =2.56, 95% CI 2.07-3.16; parents’ e-cigarette use: aOR =1.54, 95% CI 1.17-2.02) were significantly associated with their intention to use e-cigarettes. More girls were exposed to e-cigarette sales in the malls, e-cigarette information at points of sale and on social media (P<0.01), and exposure to sales from ≥2 sources were associated with girls’ intention to use e-cigarettes (aOR=1.84, 95% CI 1.22-2.78). However, boys were more likely to be exposed to friends’ e-cigarette use (P<0.001), and having friends using e-cigarettes was associated with greater intention to use them in boys (aOR=2.64, 95% CI 1.97-3.55). Less vocational high school students were exposed to parents’ e-cigarette use (P<0.001), but they were more likely to use e-cigarettes in the future after being exposed (aOR=2.27, 95% CI 1.50-3.43). A similar phenomenon was observed between junior high students and their exposure to SHA. Conclusions: This study reported adolescents’ high exposure rates to the social environment of e-cigarettes. Exposure to SHA, e-cigarette sales from ≥2 sources, e-cigarette information from ≥2 sources and having a social e-smoking environment were related to adolescents’ intention to use e-cigarettes. Differences in gender and school type were observed. More attention should be paid to girls, and different interventions should be designed for different types of school students. Additionally, comprehensive tobacco control policies are needed.